A Symptom-based COVID-19 Diagnostic Tool in case of Limited Testing Facilities - Ridwan, Raiiq; Amin, Md Robed; Rahman, Md Ridwanur (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Since December 2019, when a cluster of atypical pneumonia cases were identified in Wuhan, China a new disease has spread across the world. COVID-19 has since become the biggest pandemic in a century, touching lives in almost every country in the world. At the outset of COVID-19, the World Health Organization advised for testing to become a priority so that patients with COVID-19 could be quickly identified, isolated and treated to interrupt transmission of disease. However, testing shortages have been an increasing problem in low and middle income countries. Even when tests are available, it has proved time-consuming. Therefore, we propose a symptom-based tool to assist in the diagnosis of COVID-19 management in low and middle income Countries. It is based on the symptoms that have so far been described in the literature and advises the frontline healthcare worker on how to diagnose the likelihood of having COVID-19 and separate the patient into Red (very likely), Yellow (possible) and Green (unlikely) categories. J Bangladesh Coll Phys Surg 2020; 38(0): 71-75